2006
DOI: 10.1128/aem.01507-06
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Transfer of Bacterial Endosymbionts between Tsetse Fly Species: Infection Establishment and Effect on Host Fitness

Abstract: Tsetse flies (Glossina spp.) can harbor up to three distinct species of endosymbiotic bacteria that exhibit unique modes of transmission and evolutionary histories with their host. Two mutualist enterics, Wigglesworthia and Sodalis, are transmitted maternally to tsetse flies' intrauterine larvae. The third symbiont, from the genus Wolbachia, parasitizes developing oocytes. In this study, we determined that Sodalis isolates from several tsetse fly species are virtually identical based on a phylogenetic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 42 publications
2
72
1
Order By: Relevance
“…Based on genome comparison studies and phylogenetic analyses, Sodalis and SOPE form sister taxa (8). Interestingly, our results from multiple PCR-amplification experiments indicate that OmpA SOPE is highly homologous to OmpA Sodalis but has been rendered a nonfunctional pseudogene.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Based on genome comparison studies and phylogenetic analyses, Sodalis and SOPE form sister taxa (8). Interestingly, our results from multiple PCR-amplification experiments indicate that OmpA SOPE is highly homologous to OmpA Sodalis but has been rendered a nonfunctional pseudogene.…”
Section: Resultsmentioning
confidence: 76%
“…The symbionts included were Sodalis; CMS, a new lineage from the bloodsucking fly Craterina melbae (4); SOPE, the principle endosymbiont associated with the weevil, Sitophilus oryzae (5); Candidatus Hamiltonella defensa, a facultative symbiont found in many aphid species (20); and Photorhabdus luminescens, which is a mutualistic symbiont of heterorhabditid nematodes (21). Previous phylogenetic analysis indicated that the included symbionts form a distinct lineage related to the enteric pathogens (8). The first 171 aa of OmpA E.coli form eight membrane-traversing ␤-barrels connected by four loops (L1-L4) that are exposed to the external environment (22).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations